Optimizing Da’wah Management in Multicultural Contexts: Lessons from PCNU Pematang Siantar North Sumatra, Indonesia - Muhammad Abbas; Syukur Kholil (Bulletin of Indonesian Islamic Studies, 2025)
This study examines the da'wah management practices employed by the Pematang Siantar Nahdlatul Ulama Branch Management (PCNU) in promoting multicultural da'wah programs within a community characterized by ethnic, cultural, and religious diversity. The research utilizes a qualitative approach and adopts descriptive methods. Data collection was carried out through in-depth interviews, participatory observation, and documentation. The analysis of the data involved identifying emerging key themes and utilizing triangulation to ensure the accuracy and validity of the findings. The primary informant in this study was the chairman of the Pematang Siantar PCNU. The results indicate that PCNU Pematang Siantar has effectively implemented adaptive da'wah management practices that address cultural and religious diversity in the region. This success can be attributed to meticulous planning, structured organization, effective leadership, continuous supervision, and periodic evaluation, as well as the adjustment of da'wah methods to suit specific contexts. This research recommends the da'wah management model utilized by PCNU Pematang Siantar as a noteworthy example for other religious organizations facing the challenges of da'wah in a pluralistic society.